Implementation of K-Means Algorithm with Clustering Method to Data Management of Covid-19 Case in West Bandung Using Orange Application - Sitorus, Michael; Indah Purnamasari, Windi; Ebenhaezer Gurning, Benyamin; Ahada, Roby (ENCRYPTION: Journal of Information And Technology, 2023)
Covid-19 cases in Indonesia have not disappeared to the until now. Coronavirus has spread to almost all provinces in Indonesia, one of the province is West Java. There are 27 regencies/cities in West Java that have become the spread of the Covid-19 case, one of which is West Bandung Regency. To make it easier for the regional government of West Bandung Regency to take action in an effort to prevent the spread of Covid-19, research is needed to determine the level of distribution of Covid-19 cases which are divided into 3 clusters, namely high, medium and low clusters. Researchers analyzed using the data mining method with the K-Means Clustering algorithm through the Orange Application. Data processing is started from determining amount of the data to be clustered into 3 high, medium and low, then determining the initial centroid cluster center point (iteration 1) that has been determined randomly, then calculating the distance of each data to the center of the cluster between objects to closest centroid. The distribution of cluster 1, cluster 2, and cluster 3 as many as 16 data in the K-Means Clustering process using the Orange Application. The research results show that there are 8 sub-districts for high clusters, 2 sub-districts for medium clusters and 6 sub-districts for low clusters in West Bandung Regency.